THE IMPACT OF COVID-19 ON LEGAL EDUCATION IN INDONESIA - Heningtyas, Rifana; Pradnyawan, Sofyan Wimbo Agung (Faculty of Law, Khairun University, 2022)
Indonesia is one of the countries infected with the Covid-19 pandemic. Corona virus 2019 (COVID-19) is an infectious disease caused by acute corona virus 2 respiratory syndrome (SARS-CoV-2). So that the impact on the community and students can not meet directly on campus or in public places. Based on Nielsen's research entitled